Tuberin regulates p70 S6 kinase activation and ribosomal protein S6 phosphorylation. A role for the TSC2 tumor suppressor gene in pulmonary lymphangioleiomyomatosis (LAM) - Goncharova, Elena A; Goncharov, Dmitry A; Eszterhas, Andrew; Hunter, Deborah S; Glassberg, Marilyn K; Yeung, Raymond S; Walker, Cheryl L; Noonan, Daniel; Kwiatkowski, David J; Chou, Margaret M; Panettieri, Jr, Reynold A; Krymskaya, Vera P (The Journal of biological chemistry, 2002)
Although the cellular functions of TSC2 and its protein product, tuberin, are not known, somatic mutations in the TSC2 tumor suppressor gene are associated with tumor development in lymphangioleiomyomatosis (LAM). We found that ribosomal protein S6 (S6), which exerts translational control of protein synthesis and is required for cell growth, is hyperphosphorylated in the smooth muscle-like cell lesions of LAM patients compared with smooth muscle cells from normal human blood vessels and trachea. Smooth muscle (SM) cells derived from these lesions (LAMD-SM) also exhibited S6 hyperphosphorylation, constitutive activation of p70 S6 kinase (p70S6K), and increased basal DNA synthesis. In parallel, TSC2-/- smooth muscle cells (ELT3) and TSC2-/- epithelial cells (ERC15) also exhibited hyperphosphorylation of S6, constitutive activation of p70S6K, and increased basal DNA synthesis. Re-introduction of wild type tuberin into LAMD-SM, ELT3, and ERC15 cells abolished phosphorylation of S6 and significantly inhibited p70S6K activity and DNA synthesis. Rapamycin, an immunosuppressant, inhibited hyperphosphorylation of S6, p70S6K activation, and DNA synthesis in LAMD-SM cells. Interestingly, the basal levels of phosphatidylinositol 3-kinase, Akt/protein kinase B, and p42/p44 MAPK activation were unchanged in LAMD-SM and ELT3 cells relative to levels in normal human tracheal and vascular SM. These data demonstrate that tuberin negatively regulates the activity of S6 and p70S6K specifically, and suggest a potential mechanism for abnormal cell growth in LAM.